Systems Thinking for Principals of Learning- Focused Schools (Journal of School Administration Research and Development, 2019)
Systems thinking involves attempts to understand and improve complex systems, examines systems holistically, and focuses on the way that a system's constituent parts interrelate. This essay provides examples of how systems thinking can enable principals to demonstrate instructional leadership and nurture learning-focused schools in the current era of complexity, diversity, and accountability. These examples illustrate how systems thinking contributes to developing school curriculum, empowering professional learning communities, and fostering performance data interpretation. Overall, systems thinking offers a comprehensive way of both conceptualizing and practicing leadership for learning within the entire school setting, which leads directly to enhancing the quality of instruction and raising students' achievement.